Radiofrequency Microneedling for Skin Tightening of the Lower Face, Jawline, and Neck Region. Issue 12 (29th December 2022) - Nguyen, Lynhda; Blessmann, Marco; Schneider, Stefan W.; Herberger, Katharina
Abstract : BACKGROUND: Radiofrequency microneedling (RFMN) treatment is the latest generation of fractional skin rejuvenation methods. OBJECTIVE: To evaluate the efficacy, safety, tolerability and patient satisfaction of RFMN treatment for skin rejuvenation of the lower face and neck area. MATERIALS AND METHODS: A prospective, intraindividual, controlled study. Subjects were treated with a fractional insulated RFMN system with 1 to 3 sessions at intervals of 4 to 12 weeks. Follow-up visits were scheduled on Day 90 and 180 posttreatment. Outcome was assessed by volume analysis of standardized 3-dimensional imaging, and validated clinical scales were rated by the physician, a blinded investigator, and patients. RESULTS: Thirty patients (mean age 55.5 years, Fitzpatrick skin type I–IV) were included. Mean submental volume difference was −4.72 cm 3 (±10.07 cm 3 ; range −26.65 cm 3 to +16.01 cm 3 ). Physician, blinded investigator, and subjects rated the clinical outcome as highly improved. Mean pain intensity was 5.61/10 on Numeric Rating Scale. Beside slight swelling and redness, no relevant downtime has been observed. CONCLUSION: Fractional RFMN treatment is a safe and effective technique for rejuvenation of the lower face, jawline, and neck region. Sufficient pain management should be provided. Data indicated low to no downtime and high patient satisfaction.